2020
DOI: 10.3390/cancers12082036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Location of Tumor in the Prognosis of the Pancreatic Cancer

Abstract: Identification of prognostic factors is important to improve treatment outcomes in pancreatic cancer. This study aimed to investigate the effect of the location of pancreatic cancer on survival and to determine whether it was a significant prognostic factor. Altogether, 2483 patients diagnosed with pancreatic cancer were examined. Comparative analysis of clinicopathologic characteristics, survival analysis, and multivariate analysis were performed. Cancers of the pancreatic head or the uncinate process were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The prognosis between head PDAC and body/tail PDAC were extremely controversial. Some studies indicated primary head PDAC has a better prognosis than body/tail PDAC [ 5 , 6 ], while others suggested the opposite outcome in resectable or early advanced PDAC [ 7 , 8 ]. As the comprehensive studies revealed 4 molecular subtypes of PDAC, squamous, pancreatic progenitor, immunogenic, and aberrantly differentiated endocrine exocrine (ADEX), the squamous subtype was associated with a poor prognosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis between head PDAC and body/tail PDAC were extremely controversial. Some studies indicated primary head PDAC has a better prognosis than body/tail PDAC [ 5 , 6 ], while others suggested the opposite outcome in resectable or early advanced PDAC [ 7 , 8 ]. As the comprehensive studies revealed 4 molecular subtypes of PDAC, squamous, pancreatic progenitor, immunogenic, and aberrantly differentiated endocrine exocrine (ADEX), the squamous subtype was associated with a poor prognosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The management of pancreatic cancer has evolved over the years to incorporate multidisciplinary care and numerous treatment modalities. Despite the treatment advances, the overall 5‐year survival rate of pancreatic cancer was reported to be 8.1% 2 . Although tumor resection is considered the only curative treatment option, approximately 60% to 80% of pancreatic cancer cases are not candidates for resection because they are already locally advanced or metastatic at the time of diagnosis 3‐5 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the treatment advances, the overall 5-year survival rate of pancreatic cancer was reported to be 8.1%. 2 Although tumor resection is considered the only curative treatment option, approximately 60% to 80% of pancreatic cancer cases are not candidates for resection because they are already locally advanced or metastatic at the time of diagnosis. [3][4][5] Locally advanced (unresectable) pancreatic cancer (LAPC), which is surgically unresectable due to local involvement of adjacent vessels, accounts for 30% of all newly diagnosed pancreatic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the primary tumor location may have a significant impact on prognosis in colorectal and gastric cancer (19,20), whereas its influence in PDAC remains controversial. Some previous studies have demonstrated that differences existed in the biological and oncological behavior and prognosis between head/uncinate and body/tail PC (6,7,(21)(22)(23)(24)(25), while other studies (9,26,27) identified no significant correlation between primary tumor location and OS. Huang et al (27) analyzed 11,837 patients with chemotherapy and surgical resection from five different countries, indicating that tumor location had no influence on survival.…”
Section: Discussionmentioning
confidence: 91%